Pengaruh Tingkat Pendidikan, Ekonomi Keluarga dan Faktor Sosial Budaya Terhadap Peningkatan Pernikahan Dini Pada Masyarakat Muslim Kota Banjarmasin Provinsi Kalimantan Selatan - Maharani, Dewi; Zain, Anwar (ITB AAS INDONESIA Surakarta, 2023)
Marriage is a special event that occurs in the life of someone who does it. Marriage is the beginning of the life of a new couple who are married to compose a new story in a long journey of life with the same hope for blessings from Allah swt. In Indonesia, especially the province of South Kalimantan, in the last 3 years, the number of early marriages has increased. the number of early marriage rates in 2018-2021 is the city of Banjarmasin as the largest contributor in South Kalimantan Province. In this study using primary data sources taken directly from the respondents. Respondents in the study were Muslim communities in the city of Banjarmasin. The data collection technique uses a questionnaire with multiple linear regression tests. The results showed that the level of education had a positive influence on the increase in early marriage with a coefficient of 0.822, the coefficient for the level of education was the highest when compared with the coefficients on other variables. The results of testing the hypothesis produce a calculated t value of 5.147 > t table 1.673 with a significant value of 0.000. Family Economy does not have a positive effect on the Increase in Early Marriage while Socio-Cultural Factors have a positive influence on the Increase in Early Marriage with a coefficient value of 0.245 with t count 2.504 > t table 1.673 with a significant value of 0.015